Kontekstualisasi Hukum Waris di Indonesia: Tinjauan Maqashid Syari - Norhayati, Norhayati; Anshary, Hafiz; Umar, Masyitah (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2021)
This article aims to analyze the renewal of Islamic inheritance law in the Compilation of Islamic Law (KHI) regarding inheritance rights for fathers from the perspective of ijtihad, maslahah, and maqashid sharia. This study is a part of legal research using the library method. The approach used in this study is historical and juridical normative. The data obtained were then analyzed with the interactive qualitative analysis of the Miles and Huberman model, namely data reduction, data verification, and concluding. This study found that the provision of the father's inheritance was rejected as a valid product of ijtihad. Viewed from the perspective of maqashid al-syar'iyyah, this provision does not at all try to maintain the five basic principles above, both the maintenance of religion (din), soul (nafs), reason (aqal), offspring (nasab), property (mal). On the other hand, these provisions only bring harm.Keywords: